CRIMINAL ACCOUNTABILITY OF MEMBERS OF THE ARMY AS PERPETRATORS OF CYBERPORN IN THE PERSPECTIVE OF CRIMINAL LAW - Mau, Hedwig Adianto (FOCUS: Jurnal of Law, 2023)
The misuse and negative impact of advances in information technology through computerized systems and internet networks known as Cybercrime gave birth to a new form of crime in the form of Cyberporn which expanded its impact so that members of the TNI also committed this type of crime. This research aims to find out: (1) law enforcement against TNI members as perpetrators of Cyberporn, and (2) criminal liability against TNI members as perpetrators of Cyberporn. This research is a descriptive law with a statute approach and legal analysis (analyhical approach). The specifications of this research are prescriptive and applied. The data used is secondary data from primary and secondary legal materials. Data analysis used in this legal writing is by using the syllogism method which uses deductive thinking patterns. The research results show that: (1) The crime of pornography actually has a clear legal umbrella, including the Criminal Code, Pornography Law, ITE Law, Press Law, Broadcasting Law, Film Law, PP Film Censorship Institute, Telecommunications Law. However, there is no legislation that regulates comprehensively for cyberporn cases, and (2) The legal consequences that will be obtained by TNI members who commit cyberporn crimes are clearly regulated in the ITE Law, namely regulated in article 45 paragraph 1 of Law number 11 of 2008 which is amended by Law number 19 of 2016 article 45 paragraph 1 and also in accordance with the article on the Military Criminal Code (KUHPM) in the form of criminal sanctions and other sanctions such as dishonorable discharge (PTDH), reduction of performance allowances to salary cuts and so on.